Biological Applications of Nanoparticles Synthesized via Olea europaea Plant: A Comprehensive Review - Alireza Khanahmad; Zohre Ebrahimi; Azadeh Abreshteh; Hamid Pajavand; Naghmeh Satarzadeh; Amin Sadeghi Dousari (International Journal of Polymer Science)
Today, the emergence of nanotechnology and its various and unique medical applications has facilitated the diagnosis and treatment of diseases. In medicine, nanoparticles have extraordinary antibacterial, antifungal, antiviral, antioxidant, and antitumor properties. The nanoparticles’ unique properties depend greatly on the synthesis method because it determines the shape, size, and properties of the nanoparticle. In recent years, the green nanoparticle synthesis method has been considered a substitute for chemical and physical methods; the green synthesis of nanoparticles using plants has attracted the attention of many researchers worldwide because these methods are environmentally friendly, easy to perform, safe, energy-efficient, and affordable. One of the plants known for a long time, whose many healing properties have been widely mentioned, is the Olea europaea plant. This review is aimed at examining the studies that have used the Olea europaea plant in the green synthesis of nanoparticles and investigating the biological applications of these nanoparticles.